Effect of Azospirillum spp. and Azotobacter spp. on the growth and yield of strawberry (Fragaria vesca) in hydroponic system under different nitrogen levels - Darwin Rueda, Gabriel Valencia, Norman Soria, B. Bryan Rueda, Bangeppagari Manjunatha, Rajesh R. Kundapur, Mariadoss Selvanayagam & (Journal of Applied Pharmaceutical Science, 2016)
It is well established fact that bacterial species promotes plant growth. This growth enhancing activity was believed to be through different mechanisms such as synthesis of phytohormones, nitrogen-fixing, and biological control. For this reason, in this present investigation we have isolated and identified Azotobacter spp. and Azospirillum spp. through macromorphologically and micromorphologically in order to assess its effect on growth and yield of strawberry (Fragaria vesca) an Albion variety in hydroponic system. The inoculation and co-inoculation of bacterial culture was performed in combination with three nitrogen levels (50, 100 and 150 ppm), growth parameters such as plant height, root length, fresh and dry weight of root and aerial parts, leaf area, chlorophyll content, nutrient content, solid soluble, caliber, yield/plant. It is observed that in T8 (co-inoculation in100 ppm N) group showed significantly increase in plant height (18.57cm), chlorophyll content (48.57 Soil Plant Analysis Development-SPAD), fresh root weight (25.82g) and dry root weight (5.93g), while in treatment group T5 (Azotobacter spp. 100ppm of Nitrogen) and T6 (Azotobacter spp. 150ppm of Nitrogen) showed significant increase in root length, leaf area, dry and fresh weights of aerial parts. The N content of leaf for all treatments was in the ranges of 2.42 - 2.83 % that is suitable for cultivation. Similarly, the treatment group T5 and T6 showed increase in yield per plant and soluble solids content. So, Azotobacter and Nitrogen treatment has growth related benefits in strawberries under hydroponic system.
Keywords: Azospirillum spp.,Azotobacter spp.,Inoculation,Nitrogen,Growth,Yield,SPAD.